Keratinocyte carcinoma in organ transplant recipients. (1st November 2019) - Menzies, S.; O'Leary, E.; Callaghan, G.; Galligan, M.; Deady, S.; Gadallah, B.; Lenane, P.; Lally, A.; Houlihan, D.D.; Morris, P.G.; Sexton, D.J.; McCormick, P.A.; et al.
Summary: Skin cancer commonly affects people who have received a solid organ transplant (heart, lung, liver and kidney). Transplant patients can get multiple skin cancers, some of which can grow very quickly. The commonest types of skin cancer are basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). Immunosuppressant medication is used to prevent rejection of the transplanted organ. This alters the body's immune system, which in turn means that transplant patients are more prone to skin cancers that can grow rapidly. Over the last 20 years, newer immunosuppressants have been introduced which are thought to lessen the risk of skin cancer. Previous studies have shown a lower risk of SCC with the newer medication, but no study to date has looked at BCC rates. This study, from Ireland, aimed to find out if the rate of skin cancer in transplant patients has reduced over the last 20 years, spanning the introduction of newer immunosuppressive medications. The National Cancer Registry of Ireland registers all skin cancers for the Republic of Ireland. The authors looked at the rate of skin cancer in people who received a solid organ transplant and compared this to the rate of skin cancer in the general population. They found that the rate of SCC and BCC in patients who received an organ transplant has significantly reduced over the last two decades. This change in risk of skin cancer coincided with changes in immunosuppressant medication, along with focused education and regular skin cancer screening for transplant recipients. Abstract : Linked Article: Menzies et al. Br J Dermatol 2019; 181 :983–991